CAUSES OF INJURIES AT THREE LEVELS IN COMPETITIVE FOOTBALL - Sinku Kumar Singh (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The present study deals with comparison of causes of injuries among three groups of competitive footballers. Accordingly three groups of footballers were targeted. International, National and State groups footballers aged between 14 to 30 years. The data was collected with the help of questionnaires prepared by Cromwell, F.J. Walsh Gromley for Elite Gaelic footballers (2000) and it was modified by the investigator and utilized. In this study total 300 hundred players were targeted ; of which 100 footballers of each group. Total 318 injuries out of 300 hundred footballers were found out over the one year period; 125 injuries out of 84 footballers were found in international group footballers. 108 injuries out of 82 footballers were found in national group and 85 injuries out of 78 footballers were found in State group. The mean (SDs) age of International group to State group footballers were 21.25 (7.08), 23.33 (7.78) and 19.91 (6.29) in years respectively. Their weight were 58.35 (18.45), 58.23 (19.01), and 53.99 (17.33) kg. respectively, their height were 167.33 (55.33), 166.09 (55.10) and 164.87 (54.66) cm. respectively, their training were 4.61 (1.47), 4.31 (1.43), and 4.10 (1.33) days in a week respectively, their training durations were 2.74 (.58), 2.34 (.78), and 1.99 (.66) hours respectively, their warm-up were 28.53 (9.33), 36.05 (11.05) and 22.8 (7.8) minutes respectively, and competition was 8.67 (2.81), 8.68 (2.78), and 6.58 (2.11) in one year respectively. The results revealed that only significant difference of occurrence of injuries was found (F=3.65, P <.05) in foul play. International group footballers were found to have got more occurrences of injuries as compared to the state group footballers. The study suggest that their was no fair play at high level competition. However, no significant difference of occurrence of injuries were observed among three groups of competitive footballers with respect to causes like collision, running, contact with ball, stumble, tackle and kicking the ball.